Two Distinctions That Help to Chart the Interplay Between Conscious and Unconscious Volition - Slors, Marc (Frontiers in Psychology, 2019)
Research initiated by Benjamin Libet suggests that short-term conscious intentions are not the onsets of bodily actions. However, other research, particularly on longer term intentions, seems to show that at least some conscious intentions are effective. This leads to the idea that volition is a complex interplay between conscious and unconscious processes. The nature and structure of this interplay is mostly uncharted territory. In this paper, I will highlight two currently neglected distinctions that will help to chart the territory. The first distinction is between intentions we become conscious of (passive) and consciously formed intentions (active). The second is Fred Dretske’s distinction between structuring and triggering causes. I will introduce both distinctions by discussing how they tie in with and strengthen recent criticism of free selection paradigms and support the idea that consciously self-initiated action issues from processes of conscious deliberation and/or information integration. I will argue that consciously self-initiated action typically involves consciously formed intentions that are the structuring causes of our actions. This notion of conscious intentional action allows us to identify at least four stages in which unconscious processes co-determine our actions—without undermining their self-initiated character.